The role of the Saudi Red Crescent in spreading the culture of first aid among school and university students (The Review of Diabetic Studies, 2025)
This research aims to examine the role of the Saudi Red Crescent in spreading the culture of first aid among school and university students, as one of the most important national entities contributing to enhancing health awareness and developing skills for properly handling emergency situations before the arrival of specialized medical teams. The study relied on the descriptive analytical approach, where data was collected using a field questionnaire consisting of four main axes that addressed public awareness of first aid, the role of the Saudi Red Crescent, participation and implementation, and the impact of awareness campaigns. The tool was applied to a sample of (250) participants from school and university students in different regions of the Kingdom of Saudi Arabia, with the aim of measuring the level of awareness and the effectiveness of the programs provided. The results showed that participants' awareness was high, and that most of them recognized the importance of learning first aid skills and their ability to apply them in simple situations. The results also showed that Saudi Red Crescent programs played a prominent role in instilling a culture of first aid through media campaigns and training courses targeting young people in particular. Participants also indicated their desire to increase practical training opportunities within educational institutions. In light of the findings, the study recommended the inclusion of first aid programs in school curricula and the strengthening of partnerships between the Red Crescent and educational institutions to ensure the sustainable dissemination of this culture. This would contribute to building a more aware society capable of handling emergency situations with confidence and responsibility.